O bom professor para alunos da universidade tecnológica: interfaces da autoavaliação institucional - Rovaris, Nelci Aparecida Zanette (2013)
There are several ways to study the teaching practice. The educational environment is full of recipes, models and ideals as to be or to constitute a good teacher. This good teacher model is influenced by the pedagogical tendencies that are linked to the political, social and economical processes that build the State and the society. Under theses influences, the studies about the teaching profession reveal as different educative projects produced different expectations for the teacher´s role. From then, there were several denominations of the teacher models historically constructed. Nowadays, the concept of good teacher has become important because it shows how to construct a good teaching, a quality teaching, introduced in the institutional projects, in curriculum, in the educational technology and in the school reform. Interspersed in the historical construction concept of a good teacher and teaching, dawns the debates about the institutional evaluation, one of the proposals of this paper, that launches a privileged look to unveil the institutional self-evaluation as a tool capable to provide elements of pedagogical intervention for the configuration of a good teacher. The research presented composes the Master in Education, in the Teachers´ Formation line, and it aims to know, through the registers in the institutional evaluation, how the student of the Technological University sets the good teacher. In this context, we ask: What skills of a good professor are brought up by the academics of the Technological University in the self teaching practice selfevaluation process? How can the results of the institutional self-evaluation process collaborate in the configuration of a good university professor? As theoretical reference about institutional evaluation were used the ideas of Dias Sobrinho (1995; 2003; 2010), Belloni (1995), Ristoff (1995), Cunha (1997) Simões (2000) among others that approach this theme. As to the referential about the meaning of a good teacher,fundamentals based in authors as Cunha (1994; 2005), Freire (1996), Castanho (2001), Nóvoa (1995; 2009), Pachane (2012), Tardif e Lessard (2005), Tardif (2007), Connell (2010) and others were used. The methodology used followed the technique of case study and analysis of content based in Bardin (1977). The result shows the following skills/attributes of the good professor of the Technological University: the good professor should have deep knowledge of his discipline, the good professor must explain the content very well and the good professor must keep good relationship with his students. Considering this result, it is understood that the Institutional Evaluation in the formative conception may see and engender several ways to consolidate actions for the teaching training that lead to the professionalization of the university professor, especially of the Technological and Professional Education